The Role Of MOOCS In Enhancing Teachers' Professional Development - Permana, Dian; Afriany, Dina (Journal Socio Humanities Review, 2024)
MOOCs play a vital role in enhancing teachers' professional development by offering ongoing online learning opportunities that provide reflection and empowerment. One such initiative provided by Kemdikbudristek to facilitate teacher professionalism is the "Merdeka Mengajar" Platform. This study aims to determine how MOOCs can enhance teacher professionalism. The research method used is qualitative descriptive with the involvement of 307 teachers teaching in the city of Palembang. A questionnaire consisting of 12 statements was used to gather teachers’ opinions on the "Merdeka Mengajar" platform released by the Ministry of Education of the Republic of Indonesia, on the teacher learning and sharing platform, and on other MOOCs they have undertaken for their professional development. To see the relationship of MOOC-based learning with the improvement of teacher professionalism. The research results show a positive response from teachers towards the "Merdeka Mengajar" platform. This is evidenced by 75% of teachers stating that MOOCs provided by Kemdikbudristek have provided new knowledge about the rapidly advancing Science and Technology, increased digital literacy, and guided teachers in utilizing artificial intelligence in the development of teaching materials. The "Merdeka Mengajar" platform has positive implications for teacher professional competencies. Keywords: professionalism, teachers, "Merdeka Mengajar" platform, MOOC